Peace Agreements: Instruments of Resolving Conflict in Israeli-Palestinian Conflict - ISHAMALI , Isaac; OKOI, Ibiang (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
The Israeli-Palestinian conflict, together with a few others, has been a permanent sore in the world for over a century now. The generations of men and women were born, went about their daily chores, and passed on the legacy of conflict to the next one before they went to their graveyards. In comparison with the duration of their conflict, the period of Israeli-Palestinian diplomatic interaction has been merely about three decades. There have been many interactions on as many topics and issues, but peace remains as elusive as it was at the beginning of the process. Why this should be so is largely because the exaggerated insecurities of both parties have led to a situation where the tendency is rather to address technicalities than to go beyond them. Due to the most recent conflict between Hamas and the Palestinian militant group, which started with a terrorist attack on Israeli land, this work investigates the peace agreements and the instruments for conflict resolution in the Israeli-Palestinian conflict. This article begins with a brief overview of the conflict before examining the numerous peace treaties that the two parties have so far agreed to. The work will go in-depth on those contentious problems that haven’t found a solution. This paper argues that it is crucial that the Arab world, the Western world, and the UN work together to find a long-term solution to the issue. In this instance, the Arab League and the West will be involved in discussions about resolving the protracted war that has resulted in thousands of fatalities, rather than Palestine and Israel being treated unequally.